PREFERENSI KONSUMEN SAYUR HIDROPONIK DI KOMUNITAS HIDROPONIK SOLO RAYA - Rosita Dewati; Wahyu Adhi Saputro (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2023)
Hydroponics is an alternative plant cultivation system that used without soil. This system is quite popular with the community, especially after the Covid-19 pandemic. Many hydroponic gardens exist and survived today. Consumer preferences and behavior to consume hydroponic vegetables are certainly important for hydroponic farmers to develop their business. It is important for hydroponic farmers to know the consumer preferences of the hydroponic vegetables. By knowing this, hydroponic farmers will be able to formulate strategies for developing and marketing their businesses. This study uses conjoint analysis to determine consumer preferences for hydroponic vegetables and the combination of attributes that consumers prefer. The results of the analysis show that the order of attributes that are considered important in influencing the purchasing decision of hydroponic vegetables are 1) price, 2) weight, 3) packaging and 4) physical condition. The combination of attributes that consumers like is hydroponic vegetables with open clear plastic packaging, fresh physical condition (1-2 days after picking), weight > 300 grams per pack and a price of more than IDR 10,000.00.